Biomassa dan Estimasi Karbon Lamun Cymodocea rotundata di Pantai Rendani, Kabupaten Manokwari - Sisilia Mudarehi; Agatha C. Maturbongs; Paskalina Th. Lefaan; Maria .J. Sadsoeitoeboen; Agustinus Kilmaskossu; Fajar R.D.N Sianipar; Emmanuel Manangkalangi; Johanis P. Kilmaskossu (Badan Penelitian dan Pengembangan Provinsi Papua Barat, 2023)
Seagrass has a very important role in reducing CO2 emissions by binding carbon. Therefore, this study aims to describe biomass and estimate carbon storage of seagrass Cymodocea rotundata in Rendani Beach, Manokwari Regency, West Papua. The method used is purposive sampling using three transect lines and 30 squares measuring 30 cm x 30 cm. Biomass measurements were carried out on all squares of observations while for carbon content analysis was carried out on three squares in each transect. Carbon analysis was performed using the ashing method or Loss on Ignition. The results showed that the density of C. rotundata ranged from 44.44 - 4877.78 stands/m² and the dry biomass ranged from 13.33 - 873.33 gbk C/m². The results of the analysis showed the relationship between density and dry biomass of C. rotundata following the equation B = 196.13 + 1.6221K. Carbon estimates for this species range from 65.07 - 170.27 gbk C/m². Seagrass vegetation has an important role in storing carbon, however its presence in coastal waters has experienced many disturbances as a result of anthropogenic activities so that conservation efforts need to be made. Keywords: Cymodocea rotundata, density, biomass, ashing method, carbon storage.